The pendulum swings again: critical notes on the resource-based view - Borrero Caldas, Silvio (Cuadernos de Administración, 2010)
Research on organizational strategy can be compared to a pendulum that swings back and forth between the inside and the outside of the firm. During the brief history of strategy as an autonomous discipline, this hypothetical pendulum has oscillated completely from the inside of the organization, all the way to the external environment, and back to the firm’s core. This last swing occurred when the Resource-Based View (RBV) shifted the focus of strategic research from an environmental industrycentered perspective to a firm-centered one. Despite its evident influence on much of the strategic literature, and even though it has been the foundation for some of the most relevant studies on strategy, the RBV has probably raised more questions than it has provided answers for practicing managers. Through a review of extant literature, is identified a critical overview of the RBV that assesses its possible limitations and virtues in the context of present-day academic and management trends. To do so, the article provides a general overview of the evolution of strategic research, discusses the role played by the RBV in this story, presents some of the most salient criticisms that have been made to this perspective, and suggests possible arguments to debate such criticisms. Finally, a plausible scenario is proposed that illustrates the current state of the strategy discipline and where it seems to be heading. All things considered, extant literature and empirical evidence suggest that the strategic pendulum is swinging once again away from the organization’s core, albeit not completely. Even more relevant to theorists and practitioners alike, such apparent trend towards a balance between the inner structure and the environment surrounding the firm could be signaling a growing preference for integrative and more harmonic stances.